Multilevel Longitudinal Impacts of Incivilities: Fear of Crime, Expected Safety, and Block Satisfaction - Robinson, Jennifer B. (Journal of quantitative criminology, 2003)
Several aspects of the incivilities thesis, or the role of social and physical disorder in encouraging crime and fear, deserve further testing. These include examining individual- and streetblock-level impacts on reactions to crime and local commitment over time, and testing for lagged and co-occurring impacts at each level. We model these four types of impacts on three reactions to crime and community satisfaction using a panel study of residents ( n = 305) on fifty streetblocks, interviewed two times a year apart. At the individual level, incivilities showed unambiguous, lagged impacts on satisfaction, fear, and worry; furthermore, changes in perceived incivilities accompanied changes in resident satisfaction and fear. At the streetblock level: incivilities failed to demonstrate expected lagged impacts on either of the two outcomes where data structures permitted such impacts; changing incivilities, however, were accomp-anied by changing community satisfaction and changing perceptions of relative risk. Before we conclude that lagged ecological impacts of incivilities are weaker than previous theorizing suggests, we must resolve some outstanding theoretical and methodological issues.